2007
DOI: 10.1007/s00101-007-1249-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraartikuläre Ketamingabe bei arthroskopischen Knieoperationen

Abstract: The i.a. application of ketamine after arthroscopic knee surgery leads to a significant decrease of postoperative analgesic demand and decreases patients' subjective level of pain compared to i.a. application of bupivacaine or placebo. Likewise, the i.v. application of ketamine is similarly effective but the effect is of shorter duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…[29] Ketamine has been applied either alone or as an intraarticular adjuvant. [5,16] Several studies have confirmed the efficacy of intraarticular ketamine in postoperative pain treatment after arthroscopic knee surgery, [4,30] whereas the conflicting results are observed in another study. [31] Our meta-analysis concludes that ketamine supplementation is associated with remarkably reduced pain scores within 2 hours, analgesic consumption, and prolonged time to first analgesic requirement for knee arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Ketamine has been applied either alone or as an intraarticular adjuvant. [5,16] Several studies have confirmed the efficacy of intraarticular ketamine in postoperative pain treatment after arthroscopic knee surgery, [4,30] whereas the conflicting results are observed in another study. [31] Our meta-analysis concludes that ketamine supplementation is associated with remarkably reduced pain scores within 2 hours, analgesic consumption, and prolonged time to first analgesic requirement for knee arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…118 IA ketamine with local anesthetic demonstrates conflicting effects on pain scores and opioid use when compared to local anesthetics alone in arthroscopic knee surgeries. 119,120 IA morphine and ketorolac in addition to ropivacaine improved pain control versus ropivacaine alone 121 but not versus bupivacaine alone. 31 In hip surgery, IA clonidine injection in addition to local anesthetic did not however show a difference in pain scores or opioid consumption versus local anesthetic alone.…”
Section: Resultsmentioning
confidence: 95%
“…However, the results about the required dose and volume for administration are controversial. Huang et al[ 7 ] found that 5 mL of 0.5 mg.kg -1 intraarticular ketamine had no beneficial effect on pain scores in the first 24 h postoperatively, while Borner et al[ 10 ] demonstrated that 0.25 mg/kg intraarticular ketamine in a total volume of 10 mL effectively decreased pain scores and reduced analgesic requirement. We found that although 0.5 mg.kg -1 intraarticular ketamine in 20 mL volume combined with periarticular 10 mL 0.5% bupivacaine prolonged the time to first analgesic requirement, it had no effect on pain scores and analgesic consumption, while 1 mg.kg -1 intraarticular ketamine significantly reduced VAS scores at rest and movement and morphine consumption in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Controversial results have been published on the analgesic efficiency of intraarticular ketamine depending on the administered dose and the combination drug. [ 4 , 7 - 10 ] Huang et al[ 7 ] used 0.5 mg.kg -1 intraarticular ketamine on postoperative arthroscopic knee surgery and found no improvement in analgesia. In contrast, Salman et al[ 8 ] have compared the analgesic effect of intraarticular tramadol, magnesium, and ketamine after arthroscopic meniscectomy.…”
Section: Introductionmentioning
confidence: 99%